Isolation and characterization of neural crest stem cells from adult human hair follicles - Krejčí, E; Grim, M (Folia biologica, 2010)
Neural crest (NC) is a transient embryonic tissue, whose cells are motile and multipotent until they reach their destination and differentiate according to microenvironmental cues into a variety of cell types. However, a subpopulation of these cells remains multipotent. They were found, among other locations, in a bulge of adult murine whisker follicle and were designated epidermal neural crest stem cells (EPI-NCSCs). The aim of this work is to ascertain whether the EPI-NCSCs could be isolated from human hair follicles as well. Due to their exceptional properties, they could represent potential candidates for stem cell therapy. The presented work focuses on the isolation and characterization of EPI-NCSCs from human skin. We obtained a population of cells that expressed markers of NC, NC progeny and general stem cell markers. After prolonged cultivation, the subpopulation of cells spontaneously differentiated into some of NC derivatives, i.e. neurons, smooth muscle cells and Schwann cell progenitors. Targeted differentiation with neuregulin 1 highly increased the number of Schwann cells in the culture. Human EPI-NCSCs could also grow under non-adherent conditions and form 3-dimensional spheres. Microarray analysis was performed and gene profile of human EPI-NCSCs was compared with the list of key genes of murine EPI-NCSCs and the list of genes up-regulated in newly induced NC cells. This revealed 94% and 88% similarity, respectively. All presented results strongly support the NCSC identity and multipotency of isolated human cells. These cells could thus be used in regenerative medicine, especially because of the easy accessibility of donor tissue.
Keywords: Stem Cell Transplantation; Animals; Oligonucleotide Array Sequence Analysis; Stem Cells; vibrissae; Schwannovy buňky; Immunohistochemistry; buněčná diferenciace; lidé; Multipotent Stem Cells; transplantace kmenových buněk; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Gene Expression Profiling; Mice; kmenové buňky; neurony; polymerázová řetězová reakce s reverzní transkripcí; vlasový folikul; stanovení celkové genové exprese; kultivované buňky; myši; imunohistochemie; Neural Crest; Hair Follicle; Cells, Cultured; Neurons; Reverse Transcriptase Polymerase Chain Reaction; Vibrissae; Cell Differentiation; Schwann Cells; zvířata; crista neuralis; multipotentní kmenové buňky; Humans